Education and science: current trends - Sizykh D. S., Sizykh N. V., Kostenko E. G., Sokolov V. L., Sokolova G. A., Selianskaia G. N., Isaeva K. V., Karpova I. V., Nenakhov I. G., Iakimova I. A., Stiopkin I. I., Loginova N. A., Musorina O. A., Sorokina S. G., Fedotova P. I., Bova V. V., Rodzin S. I., Istratova O. N., Kravchenko I. A., Kureichik V. M., Lyz N. A., Koldasbaeva Z. S., Koldasbaeva Z. S., Ajkenova R. A., Betkenova M. S., Kanap'ianova A. D., Betkenova M. S. (Education and science: current trends, 2019)
the article is dedicated to the study of strategies for the polylingual personality formation. Its purpose is to describe such personality and the conditions of its formation in a multilingual educational environment. Applied methods: modeling, contrastive and comparative analysis, description. Scientific results are related to solving the problem of polylingua's various abilities formation: the formation of language, cultural and cognitive abilities of the individual are described, a frame model of the cultural and cognitive space of multilingual consciousness is built.
Keywords: способности; полилингвальная личность; полиязычное сознание; ключевая компетенция; интерференция; когнитивные структуры; языковая картина мира; polylingual personality; multilingual consciousness; abilities; key competence; interference; cognitive structures; language picture of the world